Avaliação da função cardíaca in vitro do cascudo Hypostomus regani (IHERING, 1905) e dos efeitos da exposição a concentrações subletais do pesticida Fipronil (REGENT 800WG®) - Ferro, Lucas de Abreu (Universidade Federal de São Carlos, 2014)
Fipronil (Fpn) is a phenyl-pyrazolic insecticide widely used for pest control in agriculture and livestock. It can be applied in very low doses as well as very high concentrations for the effective control of insects that show some resistance or tolerance to other families of insecticides. Fpn acts a blockers of chloride channels coupled to GABA and glutamate receptors, the latter are insect-specific targets not present in vertebrates. The aim of this study was to evaluate the possible effects on cardiac function of Hypostomus regani. of acute exposure (96 h) to sublethal concentrations (4.23 μ.Kg-1) of the pesticide Fpn, mixed into an artificial sediment. There was no difference in relative ventricular mass of the control group when compared to the group exposed to the Fpn. Ventricular strips from the Fpn exposed group exhibited showed higher twitch force (TF) and lower relationships between time-dependent variables and TF (time to peak tension - TPT/TF, and time to half relaxation - THR/TF) in response to increases in the frequency of stimulation or elevations of Ca2+ in physiological solution. Additionally, the exposed group maintained TF until a frequency of 2.6 Hz, while the TF of controls was only maintained until 2.0 Hz. Neither group showed potentiation of TF after non-physiological diastolic pause, indicating that the sarcoplasmic reticulum (RS) is not functional for contractility in this species. Corroborating that result, Western blots showed that SERCA2 was not expressed in either experimental group, these results indicate that the Ca2+ provided for ventricular contraction of H. regani is of extracellular origin. The replacement of NaCl with LiCl in saline caused negative inotropy in the exposed group, additionally, increments of Ca2+ caused positive inotropism in this group, indicating that the cardiotonic effect and greater contraction dynamics caused by exposure to Fpn were probably due to an increased expression and / or activity of NCX. Blocking of Na+/K+ pump led to a negative inotropism in both groups, presumably due to an overload of intracellular Ca2+. The cardiac pump capacity (CPC) of the exposed group was higher than the control group at all stimulation frequencies, probably due to increased activity and / or expression of NCX in the Fpn-exposed group.
Keywords: Coração - fisiologia; Hypostomus regani; Fipronil; Ecotoxicologia; Função cardíaca; CIENCIAS BIOLOGICAS::FISIOLOGIA